Censorship detected in LB (Lebanon) - Voidly (2026)
CRITICAL severity censorship detected in Lebanon. Confidence: 90%. Data sourced from OONI.
Censorship Incident ID: LB-2026-1148
Keywords: censorship; LB; censorship; critical